Highly fluorinated erbium(III) complexes for emission in the C-band - Martín-Ramos, P. (2014)
Two highly fluorinated Er3+ complexes with three 6,6,7,7,8,8,8-heptafluoro-2,2-dimethyl-3,5-octanedionate (fod) groups and either bipyridine (bipy) or bathophenantholine (bath) as the ancillary ligand emitting at the C-band (third communication window for fiber transmission) are presented. These complexes are the result of a design process aimed at decreasing the vibrational quenching from high frequency oscillators. The structure of [Er(fod)3(bipy)] has been elucidated by single-crystal X-ray diffraction, while Sparkle/PM6 and Sparkle/PM7 semi-empirical calculations have been used to model the ground state geometry for [Er(fod)3(bath)]. Photoluminescence studies confirm sensitization of the Er3+ ions by antenna effect, leading to NIR emission at 1.53 μm. This energy transfer proves to be more efficient for [Er(fod)3(bath)] as a result of the bulkier and more rigid structure of bath diimide. The good thermal stability of the materials up to over 200 °C allows envisaging their use in erbium-doped waveguides, NIR-OLEDs or other optoelectronic devices.